DONA FLOR E SEUS DOIS MARIDOS: O LIVRO E A MINISSÉRIE - Nunes, Adalgisa Maria Oliveira (2008)
This essay is focused on the analysis of Dona Flor and her two husbands, miniseries produced by Rede Globo Television in 1997 to the time of 22 hours and presented in 20 chapters. With general direction of Mauro Mendonça Filho it was adapted by Dias Gomes, with co-authors Marcílio Moraes and Ferreira Gullar from the homonym romance of the Bahian writer Jorge Amado, published for the first time in May of 1966 by the publisher Bookstore Martins, with circulation of 75 thousand copies. Our goal is to ensure quality treatment given to a specific theme, present in the novel and miniseries, that is, cooking, in the passage of the novel for television product under the focus of eroticism. As methodology, we used the qualitative method, and as a technique, the analysis of content. It was evident that from the passage of the novel to the television, cooking was depicted on a less erotised, for the book, according to the requirement of support, as well as its insertion trying to highlight the regional character of the miniseries.(AU)